2020
DOI: 10.1371/journal.pntd.0008086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical presentation and out-comes of Chikungunya and Dengue virus infections in patients with acute undifferentiated febrile illness from the Sindh region of Pakistan

Abstract: BackgroundArboviruses are a cause of acute febrile illness and outbreaks worldwide. Recent outbreaks of Chikungunya virus (CHIKV) in dengue endemic areas have alarmed clinicians as unique clinical features differentiating CHIKV from Dengue virus (DENV) are limited. This has complicated diagnostic efforts especially in resource limited countries where lab testing is not easily available. Therefore, it is essential to analyse and compare clinical features of laboratory confirmed cases to assist clinicians in sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In a cross-sectional study of arbovirus infections in Pakistan, thrombocytopenia was observed in 18% of CHIKV infections, compared to 74% in DENV. Furthermore, thrombocytosis was significantly associated with CHIKV infection (OR 2.2) [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a cross-sectional study of arbovirus infections in Pakistan, thrombocytopenia was observed in 18% of CHIKV infections, compared to 74% in DENV. Furthermore, thrombocytosis was significantly associated with CHIKV infection (OR 2.2) [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, 33.3% of arthralgia was noted in CHIKV-seropositive patients and 66.6% in combined CHIKV- and DENV-seropositive patients, but not in DENV-only cases. Arthralgia and rash have been identified as some of the typical clinical features of CHIKV although, in some cases, the infection can progress to debilitating polyarthritis that can last for months and years [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst clinicians use IgM ELISA to screen for infection, the plaque reduction neutralization test (PRNT) with ZIKV alongside DENV and other endemic flaviviruses is recommended by the Centers for Disease Control and Prevention (CDC) to confirm diagnosis in RT-PCR negative and IgM ELISA positive cases (15). However, PRNT has been shown to be challenging for diagnosis with over half of patients exhibiting significant neutralization of ZIKV, DENV, and other flaviviruses co-circulating in that region (28).…”
Section: Discussionmentioning
confidence: 99%